High-power nitrided TiO2 carbon felt as the negative electrode for all-vanadium redox flow batteries. (July 2019) - Vázquez-Galván, J.; Flox, C.; Jervis, J.R.; Jorge, A.B.; Shearing, P.R.; Morante, J.R.
Abstract: This work describes the design of an electrode with enhanced performance applied to all-vanadium redox flow batteries (VRFBs). This new electrode consists of a structural porous carbon felt decorated with TiO2 rutile nanoparticles, which has been nitrided using ammonolysis at 900 °C. An outstanding charge and mass transfer over the electrode-electrolyte interface was observed as a consequence of the synergetic effect of N- and O-functionalization over carbon felt (CF) and the partial formation of TiN (metallic conductor) phase. Moreover, this material has not only improved in terms of catalysis towards the V 3+ /V 2+ redox reaction (k0 = 1.6 × 10 −3 cm s −1 ), but also inhibited the hydrogen evolution reaction (HER), which is one of the main causes of imbalances that lead to battery failure. This led to an impressive high-power peak output value up to 700 mW cm −2, as well as work at high current density in galvanostatic conditions (i.e. 150 mA cm −2 ), exhibiting low ohmic losses (overpotential) and great redox single cell reversibility, with a superior energy efficiency of 71%. An inexpensive, earth abundant and scalable synthesis method to boost VRFBs technology based on nitrided CF@TiO2 is presented, being able to overcome certain constrains, and therefore to achieve high energy and power densities. Graphical abstract: Image 1